Анализа корелације нивоа ТГФ-β бп2 и ТНФСФ2 у серуму са тежином и предиктивном вредношћу код пацијената са хроничном срчаном инсуфицијенцијом: Нивои серума TGF-β bp2 и TNFSF2 код пацијената са хроничном срчаном инсуфицијенцијом - Liu, Yanzi; Zhu, Shidian; Bu, Wenyu; Fang, Yuzhu; Wang, Xiaochan; Liu, Fuming (Journal of Medical Biochemistry, 2026)
Objective To explore the correlations between serum ‌Transforming Growth Factor Beta Binding Protein 2 (TGF-βbp2) and ‌Tumor Necrosis Factor Ligand Superfamily Member 2 (TNFSF2) and the severity of chronic heart failure (CHF) in patients, as well as their predictive value for adverse prognosis. Methods A retrospective analysis was conducted on 240 CHF patients who were admitted to a particular hospital between January 2023 and December 2025. The New York Heart Association (NYHA) cardiac function grades upon admission were used to categorize the patients into three groups: severe (n = 70), moderate (n = 80), and mild (n = 90). FBased on the incidence of major cardiovascular adverse events (MACEs), the patients were split into two groups after the 1-year follow-up: a favorable prognosis group (n = 200) and a poor prognosis group (n = 40). The levels of serum TGF-βbp2, TNFSF2, and myocardial injury markers [cardiac troponin (cTnT), creatine kinase isoenzyme (CK-MB), and lactate dehydrogenase (LDH)] and cardiac function indicators [left ventricular ejection fraction (LVEF), left ventricular end-diastolic volume (LVEDV), and left ventricular end-systolic volume (LVESV)] were compared among the three groups and among patients with different prognoses. The correlations between serum TGF-βbp2, TNFSF2 and myocardial injury markers and cardiac function indicators were analyzed via the Person coefficient. ROC curves were built to examine the predictive value of blood TGF-β bp2 and TNFSF2 for the poor prognosis of CHF patients. Results The blood levels of TGF-βbp2, TNFSF2, cTnT, CK-MB, LDH, LVEDV, and LVESV in the severe group were greater than those in the moderate and mild groups, whereas the LVEF was lower than that in the moderate and mild groups. P < 0.05 meant that each of these differences was statistically significant. The serum levels of TGF-βbp2 and TNFSF2 were positively correlated with cTnT, CK-MB, LDH, LVEDV, and LVESV (r TGF-βbp2 = 0.342, 0.354, 0.341, 0.348, 0.340; r TNFSF2 = 0.359, 0.352, 0.351, 0.357, 0.355; all P < 0.05) and negatively correlated with LVEF (r TGF-βbp2 = -0.258; r TNFSF2 = -0.240; all P < 0.05). TGF-βbp2 and TNFSF2 serum levels were substantially higher in the poor prognosis group compared to the good prognosis group (P < 0.05). The AUCs of serum TGF-βbp2 and TNFSF2 for predicting the poor prognosis of CHF patients were 0.861 and 0.869, respectively, the AUC of the combined prediction of the two was 0.955, with a sensitivity of 90.57% and a specificity of 80.34%. Conclusion Serum TGF-βbp2 and TNFSF2 levels are positively correlated with disease severity in patients with CHF. The combined detection of these levels can achieve early prediction of poor patient prognosis.